Pengaruh Perataan Laba dan Corporate Social Responsibility Disclosure Terhadap Reaksi Pasar dan Resiko Investasi (Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia) - Agassi, Ivan Arviansyah; Prastya, Hendra; Susanto, Rindang (JOURNAL OF INTERDISCIPLINARY SCIENCE AND EDUCATION, 2023)
The market reacts to news regarding company earnings, which further suggests that earnings revisions have a negative effect on market reactions. This means that the greater the profit moderation action, the weaker the market reaction to company profit news. CSR agents cannot strengthen or weaken the relationship between income smoothing and market response. This research aims to determine the effect of income smoothing and disclosure of corporate social responsibility on market reactions and investment risk in manufacturing companies listed on the Indonesia Stock Exchange. This research focuses on problem solving to explain the relationship between one variable and another. others in qualitative and quantitative analysis. Based on the research results, it can be concluded that income smoothing does not have a significant effect on market reactions. CSR disclosure does not have a significant effect on market reactions. Income smoothing does not have a significant effect on investment risk. The moderating variables of profit and CSR disclosure, if examined together or simultaneously, do not have a significant influence on increasing market response. Based on the calculation results, it can be seen that there is a difference between investment risk and income smoothing. This disclosure will also produce positive abnormal returns because it contains information that has economic value. With the insights from this research, it is hoped that investors will be able to make investment decisions that will bring extraordinary returns to the market.